2023
DOI: 10.3389/fimmu.2023.1113560
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulation role of Th17 and Treg in renal transplantation

Abstract: Kidney transplantation (KT) is an ultimate treatment of end-stage chronic kidney disease, which can meet a lot of complications induced by immune system. With under-controlled immunosuppression, the patient will obtain a good prognosis. Otherwise, allograft disfunction will cause severe organ failure and even immune collapse. Acute or chronic allograft dysfunction after KT is related to Th17, Treg, and Th17/Treg to a certain extent. Elevated Th17 levels may lead to acute rejection or chronic allograft dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Th17 cells are a subgroup of CD4 + T cells that mediate inflammatory responses and play an important role in acute and chronic allograft rejection reactions. [27][28][29] The inability of the mother to establish pregnancy may be caused by immune rejection of the fetus by semi-allogeneic antigens, where Th17 cells play an important role. Recent studies have shown that the percentage of Th17 cells increases in patients with unexplained RSA, which may be related to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells are a subgroup of CD4 + T cells that mediate inflammatory responses and play an important role in acute and chronic allograft rejection reactions. [27][28][29] The inability of the mother to establish pregnancy may be caused by immune rejection of the fetus by semi-allogeneic antigens, where Th17 cells play an important role. Recent studies have shown that the percentage of Th17 cells increases in patients with unexplained RSA, which may be related to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells inhibit activated T cells and regulate immunity [ 21 , 22 ]. CD4 + CD25 + and FOXP3 + Treg cell expression negatively correlates with acute rejection [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 binds to IL-6R, which can then trigger downstream signal transduction and gene expression. The combination of IL-6 and TGF- β induces the retinoid-related orphan receptor (ROR) γ t, which are the key transcription factors in determining the differentiation of the Th17 lineage [ 34 ]. In this study, we showed that carnosol inhibits Th17 differentiation mainly via IL-6-IL-6R signaling.…”
Section: Discussionmentioning
confidence: 99%